The Study of Particle Size Distribution of Micronized Oat Bran Layer (Agricultural Engineering, 2020)
The aim of this work was to study the particle size distribution of micronized oat bran. An impact classified mill was used to pulverizing. Before the pulverizing raw material was sterilized using overheated steam at 150°C during 3.5 min. The moisture of bran after sterilization decreased from 7.2 to about 3.9%. Five speeds of the rotor disc were used: 2600, 2970, 3340, and 3710 rpm. For each speed of the rotor disc the following speeds of classifier wheel were applied: 480, 965, 1450, 1930, 2410 and 2890 rpm. The particle size distribution of oat bran layer was measured by laser light scattering. Moreover, the sense of touch of coarse particles of micronized oat bran on a tongue was assessed according to five point scale. The largest fragmentation of the oat bran was obtained at a disc speed of 3710 rpm and at a classifier rotation speed of 1930 rpm, whereas the most coarse particles were obtained when these parameters were 3340 rpm and 480 rpm, respectively. On the other hand, the highest uniformity in size of particles in size was observed when the lowest speed of disc and classifier were used. Moreover, for the most samples the pulverized particles of oat bran were almost not discernible on tongue.